Apples and oranges : going bananas with pairs - Pinto, Sara. (New York : Bloomsbury Children's Books : Distributed to the trade by Holtzbrinck Publishers, 2008)
Presents pairs of related items, such as an apple and an orange or a bicycle and a motorcycle, and asks why they are similar, while offering unexpected answers.
9 36
Keywords: English language -- Comparison -- Fiction; Questions and answers -- Fiction